‘Circuit Children’: The experiences and perspectives of children engaged in migrant smuggling facilitation on the US-Mexico border - Sanchez, Gabriella (Anti-Trafficking Review, 2018)
In Mexican child protection circles the term ‘circuit children’ has been used to designate people under the age of 18 who cross the US-Mexico border irregularly and cyclically for the purpose of smuggling drugs or irregular migrants. Young people of the border region have historically been involved in these markets. Yet their activities have become more visible in recent years in the context of increased border militarisation, and immigration and crime controls implemented by both the US and Mexican governments. Depicted in official and media discourses as forced recruits of local organised crime gangs, circuit children have increasingly been at the centre of initiatives that seek to identify and treat them as victims of trafficking. These efforts often rely on portrayals that frame them as gullible and defenceless, and their families and communities as inherently dysfunctional, dangerous and crime-prone. The structural and geopolitical conditions related to the children’s participation in smuggling, however, remain unchallenged. Most troublingly, trafficking discourses tend to silence the perspectives of circuit children themselves. This paper, based on interviews and participant observation, shows how circuit children, rather than seeing themselves as victims, articulate legitimate, important claims concerning their engagement in illicit markets, reflective of the ways they navigate the complex economic, socio-political and migratory contexts of the US-Mexico border.